Electronic Structure and Room Temperature of 2D Dilute Magnetic Semiconductors in Bilayer MoS2-Doped Mn - Sintayehu Mekonnen Hailemariam (Advances in Condensed Matter Physics)
The electronic structure and magnetic properties of manganese- (Mn-) doped bilayer (BL) molybdenum disulfide (MoS2) are studied using the density function theory (DFT) plus on-site Hubbard potential correction (U). The results show that the substitution of Mn at the Mo sites of BL MoS2 is energetically favorable under sulfur- (S-) rich regime than Mo. The magnetic interaction between the two manganese (Mn) atoms in BL MoS2 is always ferromagnetic (FM) irrespective of the spatial distance between them, but the strength of ferromagnetic interaction decays with atomic distance. It is also found that two dopants in different layers of BL MoS2 communicate ferromagnetically. In addition to this, the detail investigation of BL MoS2 and its counterpart of monolayer indicates that interlayer interaction in BL MoS2 affects the magnetic interaction in Mn-doped BL MoS2. The calculated Curie temperature is 324, 418, and 381 K for impurity concentration of 4%, 6.25%, and 11.11%, respectively, which is greater than room temperature, and the good dilute limit of dopant concentration is 0–6.25%. Based on the finding, it is proposed that Mn-doped BL MoS2 are promising candidates for two-dimensional (2D) dilute magnetic semiconductor (DMS) for high-temperature spintronics applications.